(untitled) (Scientific journal of the Fergana State University, 2024)
This article presents the results of studying the macro and microelement composition of processed animal hides from domestic animals in the Fergana Valley using X-ray fluorescence analysis. A total of 27 elements were quantified. Fifteen elements were identified in all studied hide samples. Higher amounts of chromium, sulfur, chlorine, silicon, and calcium were found in the hides of cattle, sheep, and goats. It was determined that the mineral content in cattle hides is 1.23 times higher compared to goat hides and 1.31 times higher compared to sheep hides. The amounts of chromium and sulfur were found to be higher in goat hides, while chlorine was more abundant in cattle hides. The macro and microelements in the processed hides provide properties such as strength, elasticity, and mechanical durability. The research results indicate that the processing of hides significantly affects their mineral composition through chemical methods.